New record and redescription of Mylonchulus paitensis Yeates, 1992 (Mononchida, Mylonchulidae) in Vietnam - Thanh Tam, Vu Thi (Academia Journal of Biology, 2025)
The species Mylonchulus paitensis Yeates, 1992 with a re-description is recorded and illustrated for the first time from Vietnam. Two populations of M. paitensis were collected from Lao Cai and Ha Giang provinces, Northern Vietnam. Their measurements and features corresponded well with the type population from Paita, New Caledonia and other populations from Iran.